MOHAMMED OTHMAN AL SAYID AND HIS POLITICAL ROLE IN LIBYA DURING THE ROYAL ERA )1952 -1969) (American Journal of Research in Humanities and Social Sciences, 2025)
The current study investigates one of the modern political persons in Libya and one of the important aspects in the Libyan history is the Royal era. It was full of inner crises, issues, and conflicts. In addition, the Arab and international changes that happened at that time. Libya became a kingdom after the declaration of its independence in 195. It witnessed a number of changes, events, and developments where its beginning was in the rule regime which became royal and was accompanied with the succession of the ministries until the coup and converting to the republican regime. This study deals with the life of Muhammed Othman AlSayid and his political role in Libya. He had an active role in the history of Libya because he became the Prime Minister during a period full of external and internal political developments. His political role started with refusing the French domination. He played a major role in the mobilization the public opinion against the French domination and their attempt to annex Fezan. Furthermore, he became a member of the Committee of Twenty-One, whose mission was to write a constitution draft for Libya, which consisted of 12 chapters within 213 items. He determined the form and regime of government. He stipulated the independence and sovereignty of Libya under a hereditary monarchy, which is named (the United Kingdom of Libya). He also held a position in the Advisory Council. He was appointed as Minister of Health in the first interim Libyan government headed by Mahmoud Al-Muntasir, where he entered a set of laws that improved the deteriorating health situation. Also, he was appointed as the Prime Minister. The most important achievement of his ministry was to amend the constitution and to transform the federal regime into a unitary regime. King Idris was convinced that the time had come to change it, so he asked AlSayid to undertake the task of transforming the regime. AlSayid also entered some changes to the items of the Libyan Constitution. He also regulated the relationship between oil companies and the Libyan government. He supported the Algerian revolution that erupted against the French domination. He announced his resignation on March 19, 1963.